2018
DOI: 10.15244/pjoes/84921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of in vitro Multiplication of Lemna minor in the Presence of Phenol: Plant/Bacteria System for Potential Bioremediation – Part I

Abstract: The aim of this work was to examine the multiplication of the common duckweed (Lemna minor), an aquatic plant species widespread in European stagnant waters, in two different media (Murashige -Skoog and Hoagland) with and without phenol supplementation. In order to quantify plant multiplication we have used relative growth rate and tolerance indices on both tested media and at five phenol concentrations (10, 15, 20, 30 and 100 mg/L). Furthermore, we examined the possibility of phenol removal from aqueous media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…Therefore, this study expands the list of phenol-degrading bacteria from the duckweed rhizosphere. Although the 4-AAP method applied in this study does not discriminate between phenolic compounds, exogenous and endogenous, according to our previous results, the amount of phenols synthesized by the plants and the microbial community under similar experimental conditions was negligible [49]. Therefore, it is our belief that the interference with the measurement is minimal.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, this study expands the list of phenol-degrading bacteria from the duckweed rhizosphere. Although the 4-AAP method applied in this study does not discriminate between phenolic compounds, exogenous and endogenous, according to our previous results, the amount of phenols synthesized by the plants and the microbial community under similar experimental conditions was negligible [49]. Therefore, it is our belief that the interference with the measurement is minimal.…”
Section: Discussionmentioning
confidence: 62%
“…The excess bleach was washed off with sterile distilled water three times. Plants (2-4 fronds) were placed on a Murashige-Skoog (MS) medium without agar (liquid medium) according to the previously applied protocol [49]. Plants were grown at 24 ± 2 • C (under fluorescent light of 40 µmoL m −2 s −1 with 16 h light/8 h dark photoperiod).…”
Section: Plant Materials and Cultivation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosive to metal, activity decreases when there is an organic material (Russell, 1990) lammable, pungent, toxic (absorbed by the entire route), (Radulovic et al, 2018) leaving residue on the surface, inactivated by hard water, reduced activity by nonionic detergents. (Mcdonnell, 2007).…”
Section: Oxidizing Agentsmentioning
confidence: 99%
“…In duckweeds, favorable modulation of antioxidative response is reported to be correlated with plant-growth-promoting abilities of bacteria [ 15 , 16 ]. Our previous studies on duckweeds also showed a promotive effect of the natural bacterial community in rhizosphere, most prominently on the plants’ multiplication [ 17 , 18 , 19 ]. However, information regarding the effect of rhizosphere-associated bacteria on the oxidative stress response of aquatic plants, especially under the conditions of abiotic stress such as phenol pollution, is still lacking [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%